Structure-Based Evolutionary Programming Design of Broadband Wire Antennas - Giovanni Andrea Casula; Giuseppe Mazzarella; Giorgio Montisci (International Journal of Antennas and Propagation)
A design technique for wire antennas, based on the Structure-Based Evolutionary Programming, is used to design a broadband antenna with an end-fire radiation pattern and a very simple geometry, operating in the 3–16 GHz frequency band, namely, from the S band to the Ku band. The antenna has been analyzed with NEC-2 during the evolutionary process, looking for high gain, good input match, and robustness with respect to realization tolerances. The outcome of our design procedure shows a very good performance.